Numerical investigation of cell encapsulation for multiplexing diagnostic assays using novel centrifugal microfluidic emulsification and separation platform - Ren, Yong; Leung, Wallace (MDPI, 2016)
In the present paper, we report a novel centrifugal microfluidic platform for emulsification and separation. Our design enables encapsulation and incubation of multiple types of cells by droplets, which can be generated at controlled high rotation speed modifying the transition between dripping-to-jetting regimes. The droplets can be separated from continuous phase using facile bifurcated junction design. A three dimensional (3D) model was established to investigate the formation and sedimentation of droplets using the centrifugal microfluidic platform by computational fluid dynamics (CFD). The simulation results were compared to the reported experiments in terms of droplet shape and size to validate the accuracy of the model. The influence of the grid resolution was investigated and quantified. The physics associated with droplet formation and sedimentation is governed by the Bond number and Rossby number, respectively. Our investigation provides insight into the design criteria that can be used to establish centrifugal microfluidic platforms tailored to potential applications, such as multiplexing diagnostic assays, due to the unique capabilities of the device in handling multiple types of cells and biosamples with high throughput. This work can inspire new development of cell encapsulation and separation applications by centrifugal microfluidic technology